Estudio de factibilidad legal y de mercado para determinar la viabilidad de la exportación de concentrado de maracuyá hacia Alemania en el 2023. - Aponte Vargas, Sheila Paola; Reyes Romero, Karen Camila (Machala : Universidad Técnica de Machala, 2024)
The lack of knowledge about business opportunities in new international markets has limited the export of products related to Ecuadorian passion fruit concentrate to new potential markets. Germany, a country with high purchasing power and a growing demand for high-quality food, has represented an interesting opportunity for producers and exporters of passion fruit concentrate. Entering a new market gives companies the opportunity to increase their profits and consolidate their position on the global business scene. Considering that Ecuador is a leader in the production and export of agricultural products. As for passion fruit, it has a privilege due to its fertile lands and its climate conducive to the production of the raw material. In addition, considering as an advantage that Germany is part of the European Union and Ecuador currently has an agreement in force, as a result of which the products benefit from tariff preferences. That is why, in this research work for titration purposes, the aim was to determine whether the export of passion fruit concentrate to Germany is a viable option, obtaining a positive answer. This study adopted a comprehensive perspective that encompasses from the international point of view technical, commercial and legal aspects, intended to serve with an exhaustive and successful guide for actors interested in the commercialization and internationalization of products derived from Ecuadorian passion fruit. To achieve this, a variety of approaches and methods were used, including theoretical methods such as historical-logical, analytical synthetic, inductive-deductive, abstraction-concreation and the systemic method that allowed to support and substantiate the research. Empirical methods such as the study of documents were also implemented, which allowed to obtain information to obtain a deep and accurate understanding based on the study carried out in the field of international trade.
La ausencia de conocimiento acerca de las oportunidades comerciales en nuevos mercados internacionales ha limitado la exportación de productos concernientes al concentrado de maracuyá ecuatoriana hacia nuevos mercados potenciales. Alemania, un país con un elevado poder adquisitivo y una creciente demanda por alimentos de alta calidad, ha representado una oportunidad interesante para los productores y exportadores de concentrado de maracuyá. Al ingresar a un nuevo mercado las empresas tienen la oportunidad de incrementar sus ganancias y consolidar su posición en la escena global de negocios. Tomando en consideración que Ecuador es un líder en producción y exportaciones de productos agrícolas. En cuanto al maracuyá se posee un privilegio debido sus tierras fértiles y su clima propicio para la producción de la materia prima. Además, contemplando como ventaja que Alemania es parte de la Unión Europea y Ecuador actualmente posee un acuerdo vigente, resultado de ello que los productos se benefician de las preferencias arancelaria. Es por ello que, en el presente trabajo de investigación con fines de titulación tuvo como finalidad determinar si la exportación de concentrado de maracuyá hacia Alemania es una opción viable obteniendo una respuesta positiva. Este estudio adoptó una perspectiva integral que engloba desde el punto de vista internacional aspectos técnicos, comerciales y legales, destinado a servir con una guía exhaustiva y exitosa para actores interesados en la comercialización e internacionalización de productos derivados del maracuyá ecuatoriano. Para lograrlo, se emplearon una variedad de enfoques y métodos, entre ellos los métodos teóricos tales como, histórico- lógico, analítico- sintético, inductivo- deductivo, abstracción-concreción y el método sistémico que permitieron respaldar y fundamentar la investigación, también se implementaron métodos empíricos como el estudio de documentos que permitió la obtención de información para obtener una comprensión profunda y precisa en base al estudio realizado en el ámbito del comercio internacional.
Keywords: ALEMANIA; DEMANDA; EXPORTACION; MARACUYA